A Comparison of Fruit Chemical Characteristics of Two Wild Grown Rubus Species from Different Locations of Croatia - Dujmović Purgar, Dubravka; Duralija, Boris; Voća, Sandra; Vokurka, Aleš; Ercisli, Sezai (Molecules (Basel, Switzerland), 2012)
The main focus of our study was to investigate differences in nutritional (dry matter, soluble solids content, total acidity and pH value) and bioactive values (ascorbic acid, total anthocyanins, total phenols, and non-flavonoids content) of wild grown raspberry (Rubus idaeus) and blackberry (Rubus discolor) genotypes harvested from native populations in Croatia. The average total acidity ranged from 0.93 to 1.72% in R. discolor and 1.57 to 1.91% in R. idaeus. Ascorbic acid was found between 22.34 mg and 45.00 mg 100 g−1 in R. idaeus, while it was between 30.64 mg and 33.09 mg 100 g−1 in R. discolor genotypes. A great variability in total anthocyanins was detected in Croatian wild blackberry and raspberry genotypes, ranging from 2,226 to 2,367 mg kg−1 for blackberries and 279 to 582 mg kg−1 for raspberries, indicating wild blackberries are particularly rich in anthocyanins. On the basis of these results, it can be concluded that investigated wild growing fruit species have a great potential in nutritive research, as well as in biodiversity research. It is necessary to carry out further investigation and evaluation of wild growing fruit species to utilize them in the most appropriate way, as well as conservation of interesting accessions in the gene banks.